Indications for Atrial Fibrillation Ablation: A Practical Guide for Non-Cardiologists - Silva Cunha, Pedro (2024)
Given the increasing incidence of atrial fibrillation and the widespread use of catheter ablation as a form of non-pharmacological treatment, we intended to provide a practical guide for non-cardiologist physicians, concerning the main indications for this intervention based on current guidelines.